2010
DOI: 10.1088/1742-6596/209/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Scanning capacitance microscopy studies of GaN grown by epitaxial layer overgrowth

Abstract: Abstract. Epitaxial layer overgrowth (ELOG) is a common technique for dislocation density reduction in GaN heteroepitaxy. Here, scanning capacitance microscopy is used to study the variations in unintentional doping arising from the ELOG process and reveals facet-dependent incorporation of n-type dopants during the initial regrowth of GaN, and then p-type doping arising from the use of bis(cyclopentadienyl)magnesium to enhance lateral growth during the coalescence stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…长(ELOG) [5][6][7][8] 和悬臂外延生长(PE) [9,10] 等诸多方法来 改善 GaN 外延薄膜的性能, 尽管 ELOG 被认为是一 种极为有效的减小线位错密度的方法, 但这种方法 耗工耗时, 且要求两步生长, 这常会引入非故意掺杂 或污染. 最近采用单步生长的图形化衬底技术成为 研究的热点, 图形化衬底技术通过在蓝宝石表面制 作具有细微结构的图形, 然后在这种图形化衬底表 面进行材料外延.…”
unclassified
“…长(ELOG) [5][6][7][8] 和悬臂外延生长(PE) [9,10] 等诸多方法来 改善 GaN 外延薄膜的性能, 尽管 ELOG 被认为是一 种极为有效的减小线位错密度的方法, 但这种方法 耗工耗时, 且要求两步生长, 这常会引入非故意掺杂 或污染. 最近采用单步生长的图形化衬底技术成为 研究的热点, 图形化衬底技术通过在蓝宝石表面制 作具有细微结构的图形, 然后在这种图形化衬底表 面进行材料外延.…”
unclassified
“…Further, without long annealing under H 2 ambient, significant morphology changes of the InGaN layers caused by the annealing effect may be avoided. [18] In order to clarify the annealing effect, sample Q1A was grown with the same processes like that for the sample Q1, but with an additional "annealing" process (ramping from 670 ∘ C to 786 ∘ C in 108 s) followed by a fast cooling process. The surface morphology of the InGaN epilayers and InGaN/GaN QWs was investigated by atomic force microscopy (AFM).…”
mentioning
confidence: 99%
“…It has been reported that the temperature ramp for the barrier growth may alter the morphology of the InGaN layer to a interlinking network of InGaN strips if annealing for a relatively long time (240-960 s) under H 2 ambient. [18] Both the prolonged annealing and the introduction of H 2 would enhance the InGaN decomposition. [20] Accordingly, in this study, relatively fast ramping (108 s) and lack of H 2 introduction were employed for the avoidance of obvious morphology changes of the InGaN layers.…”
mentioning
confidence: 99%